Emerging sodium/glucose co-transporter 2 inhibitors for type 2 diabetes. (September 2013) - Boyle, Luke D; Wilding, John PH
Abstract : Introduction: Type 2 diabetes mellitus (T2DM) is a public health challenge globally. Numerous treatments are available which can improve insulin sensitivity or stimulate its secretion including biguanides, sulphonylureas and glitazones, as well as insulin, GLP-1 agonists and DPP-IV inhibitors. These are usually unable to halt progression with high resulting morbidity and mortality. New therapies are, therefore, being developed; inhibition of glucose reabsorption from the renal filtrate has been proposed as a novel therapeutic target, and sodium/glucose co-transporter 2 (SGLT2) inhibitors have been developed accordingly. Areas covered: This review summarises the challenge that T2DM poses and describes established therapies. The market for these therapies and likely changes are examined, as well as the scientific rationale behind the development of SGLT2 inhibitors. SGLT2 inhibitors in clinical trials worldwide are reviewed and issues affecting their development are discussed. Expert opinion: SGLT2 inhibitors offer a novel therapeutic approach to the management of T2DM; advantages over other agents include weight loss and blood pressure lowering with a low intrinsic risk of hypoglycaemia. The main adverse effects likely to be seen in clinical practice are a very small increase in risk of urinary tract infections, and a modest risk of developing genital fungal infections – which appear more common in the first few months of treatment. Meta-analyses suggest no increased risk of cardiovascular disease, but longer duration outcome studies are essential to prove long-term safety and efficacy.